Organizational Conflict 2018
DOI: 10.5772/intechopen.73092
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Trust as a Conflict Management Tool in Contemporary Work Organizations

Abstract: Conflict between management and employees or among employees is an irresistible phenomenon in contemporary work organizations. Evidences gathered from past and present studies revealed that a lot of conflict situations have occurred in work organizations which have significantly impacted organizational performance and its survival in recent times. Consequently, several conventional strategies and techniques have been deployed to constructively manage conflict situation in work organization however, realities s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…The concept of trust has received considerable interest among scholars and has emerged as a leading field of research among businesses recently due to its connections with different individual and organisational outcomes (Jafri, 2012) like organisational commitment, organisational citizenship behaviours, employee loyalty, conflict management, employees' engagement, and organisational justice (Matzler and Renzl, 2006;Rhee, 2010;Ugwu Fabian et al, 2014;Wang et al, 2019;Solaja, 2018;Alshaabani et al, 2020). Thus, it can be observed that having a high level of trust matters for any organisation, and it is fundamental for its success (Brockner et al, 1997).…”
Section: Literature Review 21 Trustmentioning
confidence: 99%
See 3 more Smart Citations
“…The concept of trust has received considerable interest among scholars and has emerged as a leading field of research among businesses recently due to its connections with different individual and organisational outcomes (Jafri, 2012) like organisational commitment, organisational citizenship behaviours, employee loyalty, conflict management, employees' engagement, and organisational justice (Matzler and Renzl, 2006;Rhee, 2010;Ugwu Fabian et al, 2014;Wang et al, 2019;Solaja, 2018;Alshaabani et al, 2020). Thus, it can be observed that having a high level of trust matters for any organisation, and it is fundamental for its success (Brockner et al, 1997).…”
Section: Literature Review 21 Trustmentioning
confidence: 99%
“…Another important outcome of trust is conflict management climate; previous studies indicated that low levels of trust can create feelings of non-corporations inside an organisation which may result in organisational conflict (Solaja, 2018). According to Coleman et al (2013), trust is a direct and powerful way of enhancing a positive climate for managing conflict within organisations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The support need not be always of monetary values; factors like appreciable physical working conditions and the total working hours are part of organizational support (Richardson and Watt, 2010). Perceived organizational support also includes the perception of the employees that the management is supportive and promotes positive behaviors to circumvent conflict and ensure fairness in the workplace (Solaja, 2018). Further, when any vital change is proposed, management should discuss that with the employees upfront and should provide assistance and training where required to align with those changes (Anderson and Ackerman‐Anderson, 2010).…”
Section: Conceptualization and Instrumentationmentioning
confidence: 99%